Imaging Prenatal Diagnosis of Cleft Lip and Palate in Brazil: Frequency and Familial Impact - Karla Baba; Rayane Pinto; Gisele S Dalben (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2019)
Background and aim: The ultrasound evaluation of the fetal face for detection of orofacial clefts is the most common method for diagnosis. This study analyzed the frequency of patients whose orofacial clefts were diagnosed prenatally, concordance of prenatal diagnosis and postnatal outcomes, and the impact of prenatal diagnosis. Materials and methods: The sample was composed of 200 children (age of 0-36 months) relatives, with any orofacial cleft, regardless of ethnicity, gender or socioeconomic background. A self-administered questionnaire was responded, and the results were analyzed by descriptive statistics and Fisher exact test. Results: Among the 200 children, 25.5% had been diagnosed prenatally. There was concordance between prenatal diagnosis and outcome in 62.7% of cases, being similar for all types of clefts (p=0.81). Less than fully accurate prenatal diagnosis occurred in 37.2%. Under the 51 families that had prenatal diagnosis, 66.6% considered the opportunity as favorable. Among the favorable reasons, 58.8% of the families mentioned the possibility to prepare themselves. Conclusion: one quarter of patients were diagnosed prenatally and less than fully accurate findings occurred in more than a third of the cases diagnosed. In spite of that, families often report prenatal diagnosis as helpful for the acceptance of the condition and psychological preparation before the child is born.